Multi‐centric validation of an in‐house‐developed beacon‐based PCR diagnostic assay kit forChlamydiaandNeisseriaand portable fluorescence detector. Issue 9 (September 2018) - Sachdev, Divya; Wasnik, Kirti; Patel, Achchhe Lal; Sonkar, Subash C.; Desai, Parul; Mania‐Pramanik, Jayanti; Kerkar, Shilpa; Sethi, Sunil; Sharma, Nandita; Mittal, Pratima; Ghope, Priti; Khandhari, Ajay; et al.
Abstract : Objective. : The development of an accurate, sensitive, specific, rapid, reproducible, stable‐at‐room‐temperature and cost‐effective diagnostic kit, and a low‐cost portable fluorescence detector to fulfil the requirements of diagnostic facilities in developing countries. Methods. : We developed the 'Chlamy and Ness CT/NG kit' based on molecular beacons for the detection of Chlamydia trachomatis (CT) and Neisseriagonorrhoeae (NG). Multi‐centric evaluation of the CT/NG kit was performed using the commercially available nucleic acid amplification test (NAAT)‐based FTD Urethritis basic kit for comparison from December 2014 to November 2016. The stability of the kit reagents at 4 and 37 °C and the inter‐day reproducibility of results were also analysed. Results. : The sensitivity and specificity of the kit were found to be 95.83 and 100.00 % for the detection of C. trachomatis and 93.24 and 99.75 % for N. gonorrhoeae, respectively, when tested against the commercial kit. The positive predictive value (PPV) was 100.00 and 98.57 %, whereas the negative predictive value (NPV) was 99.54 and 98.79 % for C. trachomatis and N. gonorrhoeae, respectively. Analysis of the kappa statistics enhanced the 'inter‐rater' κ=0.976 for Chlamydia and κ=0.943 for Neisseria. Conclusion. : Our kit was found to be as sensitive and specific as commercially available kits. Its low cost and ease of use will make it suitable for the routine diagnosis of C. trachomatis and N. gonorrhoeae in the resource‐limited settings of developing countries.